EVALUATION OF DRIED MAO POMACE (ANTIDESMA BUNIUS LINN.) AND L ACTIC ACID BACTERIA AS ADDITIVES TO ENSILE STYLO LEGUME (STYLOSANTHES GUIANENSIS CIAT184) - S. Bureenok; N. Pitiwittayakul; C. Yuangklang; K. Vasupen; B. Saenmahayak; Y. Kawamoto; J. T.; Schonewille (Journal of Animal and Plant Sciences, 2019)
The effect of application of dried mao pomace (DMP), fermented juice of epiphytic LAB (FJLB), and Lactobacillus paraplantarum (LPP) on the ensiling process of Stylo (Stylosanthesguianensis CIAT184) was evaluated. Stylo silage was treated with 10% DMP alone or in combination with either FJL Bor LPP. The addition of DMP to Stylo reduced the mean pH by at least 0.9 units while the use of LAB was found to maximally reduce pH by 0.21 units. Irrespective of the source of LAB, the pH reducing effect of LAB was only observed in the silages without DMP. NH3-N contents were found to be significantly affected by DMP × LAB. The use of DMP reduced the NH3-N contents by at least 50%, irrespective of the addition of LAB. Furthermore, HBut levels were below detection limits when DMP was used as a silage additive and in case the silages were not treated with DMP, the addition of either FJLB or LPP also resulted in lower HBut fractions. In view of the high NH3-N and HBut levels, it was therefore concluded that ensiling of Stylo without DMP or LAB results in an inferior silage quality. The use of DMP as a silage additive resulted in good quality silage, irrespective of the use of additional LAB.
Keywords: Fermentation quality; Lactobacillus paraplantarum; Phenolics; Silage